2006
DOI: 10.3168/jds.s0022-0302(06)72397-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Frequency and Feeding Level on Nutrient Utilization in Heavy Preruminant Calves

Abstract: The objective of this study was to determine the effects of feeding frequency (FF) and feeding level (FL) on protein and energy metabolism in adapted, heavy preruminant calves. It was hypothesized that an increased FF would increase protein utilization by an improved synchrony between the supply of and requirements for protein during the day when a quickly hydrolyzable protein source was used. Eighteen Holstein Friesian calves of 136 +/- 3 kg of body weight were assigned to FF (1, 2, or 4 meals daily) at 2 FL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 27 publications
5
47
2
Order By: Relevance
“…Lactose is highly digestible (Burt and Irvine, 1970;Coombe and Smith, 1974;Van den Borne et al, 2006), and in a typical MR, lactose accounts for 40% of the digestible energy available to the calf. However, the volatility of lactose prices stimulates MR producers to replace lactose by other sources, particularly starch or products originating from starch.…”
Section: Introductionmentioning
confidence: 99%
“…Lactose is highly digestible (Burt and Irvine, 1970;Coombe and Smith, 1974;Van den Borne et al, 2006), and in a typical MR, lactose accounts for 40% of the digestible energy available to the calf. However, the volatility of lactose prices stimulates MR producers to replace lactose by other sources, particularly starch or products originating from starch.…”
Section: Introductionmentioning
confidence: 99%
“…However, the frequency of meals should be investigated based on animal needs and welfare. Effects of feeding frequencies on milk production and ruminal physiology have been investigated in dairy cows (Yang & Varga, 1989;Liboux & Peyraud, 1999;Shabi et al, 1999;Van den Borne et al, 2006). Keskin et al (2004) observed that Awassi lambs increased their feed intake when they were offered fresh feed even when there was feed in their feed troughs.…”
Section: Introductionmentioning
confidence: 99%
“…It was postulated that increased meal frequency with fresh feed would promote the appetite of lambs and have an influence on their finishing performance and carcass weights. In previous studies (Yang & Varga, 1989;Liboux & Peyraud, 1999;Shabi et al, 1999;Van den Borne et al, 2006) meal frequency referred to the frequency with which animals actually consume feed, not to the frequency with which animals were presented with fresh feed. The literature is inconclusive on the effect of feed refreshening on the growth performance and carcass characteristics of lambs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, fat deposition increased (Van den Borne et al, 2006a). It can be hypothesised that the higher energy expenditure of gastrointestinal tissues associated with big meals may explain the low fat deposition when calves are fed less frequently.…”
Section: Effect Of Nutrient Deliverymentioning
confidence: 99%